POLA KOMUNIKASI ANTAR BUDAYA ETNIS MINANG DAN JAWA DI NAGARI SURIAN KABUPATEN SOLOK - Rivatul Indah Yani; Januar Januar (Jurnal Komunikasi, 2024)
Indonesian culture is delegated a heterogeneous society since it comprises of different sorts of variety in completing correspondence to satisfy their life needs, cooperating both among ethnic gatherings and with others or gatherings with various social foundations, so that is where intercultural correspondence is made. In Surian, there are different networks with various social foundations living there, for example, the Minang and Javanese identities, correspondence between individuals' societies generally happens and they live next to each other. This examination was led to decide correspondence designs among Minang and Javanese ethnic societies in Nagari Surian and what elements support and repress intercultural correspondence. To figure out correspondence examples and supporting and restraining factors for correspondence in Nagari Surian, field research was utilized. Information assortment was done by perception, meetings and documentation to make it simpler to figure out correspondence examples and supporting and restraining factors for correspondence in Nagari Surian. The creator utilized the Snowball Inspecting Strategy. In view of the examination results, the example of correspondence among Minang and Javanese ethnic societies in the Surian town of Solok Regime is very great with the essential correspondence design, specifically the Minang and Javanese ethnic networks involving verbal and non-verbal correspondence in regular day to day existence. The straight correspondence design, in particular the Minang ethnic local area and Javanese convey straightforwardly or up close and personal by tuning in and seeing what is said first and afterward making determinations by checking out at their way of behaving and developments. Round correspondence designs, specifically the presence of criticism or equal connections between the Minang and Javanese ethnic networks so this seldom occurs. misreading in correspondence